Nutritional nursing competence of clinical nurses and its influencing factors: a cross-sectional study - Tang, Yuan; Wen, Xiumei; Tang, Xiaoli; Li, Xiaoxue; Zhang, Li; Duan, Shujuan; Long, Ping; Zhou, Zixuan (Frontiers in Nutrition, 2024)
ObjectiveAssessing the nutritional nursing competence of clinical nurses will enable nursing managers to develop measures to effectively address the nutritional nursing needs of patients. Therefore, the purpose of this study was to investigate the status quo and influencing factors of nutritional nursing competence of nurses in China.MethodA cross-sectional survey was conducted among more than 1300 clinical nurses from 10 provinces in eastern, central and western China by using self-designed socio-demographic questionnaire and nutrition nursing ability scale compiled by Zhu Xinyi.ResultThe median score of nurses’ nutritional nursing ability was 238 (210, 258). Univariate analysis confirmed that a total of 12 factors were shown to be statistically significant for nurses’ competency in nutritional care. The results of multiple linear regression analysis showed that department, hospital level, monthly income, learned nutrition courses, regular participation in nutrition continuing education and training, be a nutrition specialist nurse, participation in nutrition nursing knowledge and skills training, and the hospital’s regular conduct of special quality supervision of nutrition nursing and carried out special quality improvement projects of nutrition nursing.ConclusionIn China, the nutritional nursing competence of nurses is at an upper medium level and needs to be further improved. In order to improve the level of nutrition nursing, encourage and support nurses to take targeted nutrition care education and training, nursing managers should also adopt multi-mode intensive inspection and examination.